EROS AND LOGOS. Issue 3 (3rd May 2020) - Kauffman, Stuart
Abstract: For the ancient Greeks, the world was both Eros, the god of chaos and creativity, and Logos, the regularity of the heavens as law. From chaos the world came forth. The world was home to ultimate creativity. Two thousand years later Kepler, Galileo, and then mighty Newton created deterministic classical physics in which all that happens in the universe is determined by the laws of motion, initial and boundary conditions. The Theistic God who worked miracles became the Deistic God who set up the universe and let Newton's laws take over. Eros, raw creativity, is dead, all is Logos. Quantum mechanics replaced the determinism of classical physics with fundamental indeterminism. This was a major crisis in physics, but remained entirely within the Newtonian paradigm of laws, here the Schrödinger equation, initial and boundary conditions. The Schrödinger equation entails the deterministic propagation of a probability distribution. The probabilities concern the indeterminate outcomes of quantum measurement events. The central issue of this article is to show that no laws at all determine or entail the becoming of our biosphere or any other among the 10 22 solar systems in the universe. This claim is radical. If no laws determine or entail the becoming of biospheres, and biospheres are part of the universe, the Pythagorean dream that All is Number, All is Logos, is dead. There is no Final Theory that entails all that become in the universe. Eros is again, and always was, rambunctiously alive in the raw creativity of the becoming of life anywhere in the universe. The becoming of life is based on physics, on Logos, but beyond it, emerging from Eros. The reasons Eros is at play in the evolution of biospheres are fourfold. First, the universe will not make all possible complex things. That is, the universe is vastly non-ergodic. Yet complex things such as the human heart exist. Second, the reason human hearts exist is that organisms are Kantian Wholes in which the parts exist for and by means of the whole. Hearts exist because they fulfill the function of pumping the blood that keeps the whole organism alive. Such organisms propagate progeny that carry with them the hearts that keep them alive. Third, adaptations like hearts, the flagellar motor, the loop of Henle in kidneys that concentrates urine, and flight feathers, are tinkered-together contraptions stumbled upon in evolution. Parts and processes that arise in evolution are jury-rigged for unprestatable new functions that help keep the entire Kantian Whole organism alive and propagating in the evolving biosphere. There is no deductive theory of jury rigging. We cannot deduce the emergence of such novel functions. Fourth, the functions of parts of organisms emerge in unprestatable ways and form the unprestatable and ever-changing phase space of evolution. Since we cannot prestate the ever-changing phase space of evolution, we can write no laws of motion in differential equation form, so cannot integrate the equations we do not have. Thus, no laws entail the becoming of any biosphere. Evolving biospheres are everywhere creative. This is Eros, the chaos from which the world emerges. This profound creative emergence is the stuff of story, of narrative. Evolving biospheres always were and always will be both Eros and Logos, the stuff of story and the stuff of law. We always live in a world of Art and Science.